Detection of the Staphylococcal mecA gene by chemiluminescent DNA hybridization. - Kolbert, C P (1995)
A new solution-phase DNA hybridization capture assay for the rapid detection of the mecA gene in clinical isolates of Staphylococcus was compared with multiplex PCR and disk diffusion methods. The assay uses a DNA capture probe immobilized on paramagnetic particles and a second DNA probe labeled with an acridinium ester. Bacteria from 24-h cultures are lysed, and the lysates are hybridized with the DNA probes. After magnetic separation to remove unhybridized labeled probe, the mecA gene is detected by the chemiluminescence of the hybridized probe. Four hundred consecutive staphylococcal isolates were assayed, including 147 S. aureus and 253 coagulase-negative Staphylococcus isolates. Among the S. aureus isolates, 14 of 147 were MecA+ by both the hybridization capture assay and PCR; 133 of 147 were MecA negative by both assays (positive and negative predictive values, 100%). Comparison of disk diffusion results with those obtained by genotypic methods indicated that 14 of 147 S. aureus isolates judged to be resistant were positive by both methods; 119 of 147 were Oxs and negative by both genotypic methods (positive and negative predictive values, 50 and 100%, respectively). The remaining 14 S. aureus isolates were MecA- Oxr; among these, 13 were beta-lactamase hyperproducers. For coagulase-negative staphylococci, 130 of 253 were MecA+ by the hybridization capture assay; 129 of 130 of these isolates were positive by PCR (positive and negative predictive values, 99.2 and 100%, respectively). Comparison with the disk diffusion assay showed that 128 of the coagulase-negative MecA+ isolates were Oxr; 111 of 253 were MecA- and Oxs (positive and negative predictive values, 90.8 and 99.1%, respectively).(ABSTRACT TRUNCATED AT 250 WORDS)